(untitled) (Economic and Political Thought, 2013)
The article shows the complex process of building a new, multi-polar international order and Russia’s role in it, especially in the field of future peace and international security. The author presents many interesting theses and asks some research questions. For example, he states that the future international system that is being created now will not only have a multi-polar shape but will also be multi-civilizational. He also highlights that, apart from the United States and the European Union, Russia will play a very important role in the system but only if it becomes a modernized and democratic country. Thus, it is necessary to do everything not to let these entities disappear from the political map of the world and make them cooperate in order to strengthen the peace and international security. In the author’s opinion, in the nearest future Russia will be forced to cooperate with the Euro-Atlantic system and to lead a multi-directional foreign policy, i.e. to cooperation with the European Union and NATO on the one hand, and with the emerging economies, especially China and India, on the other hand. Today, Russia needs Western technologies and loans as well as Asian markets in order to carry out necessary modernization and become an important member of the “concert of powers” that will be responsible for the new international system and its security.